2001
DOI: 10.1081/ncn-100002518
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Flexibility in Pna: Dna Binding Studies With Bridged Aminopropylglycyl Pna

Abstract: Introduction of methylene bridges in aegPNA and apgPNA molecules give rise to cyclic five and six membered ring structures. Synthesis of a new six membered cyclic PNA monomer, aminopipecolyl PNA (pipPNA) is reported. Incorporation of pipPNA into PNA oligomers and comparative binding with target DNA sequences is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…1 H NMR CDCl3 δ: 7.35(s, 5H), 5.2 (d, 2H), 5-4.75(m, 1H), 4.7-4.3 (m, H6), 3.7 (m, 3H), 3.1 (m, 3H), 2.5-1.4 (m, 5H). 13 (2S,5R)-5-Azido-N-1 (Benzyloxycarbonyl)pipecolic Acid Methyl Ester 3. To the compound 2 (0.74 g, 1.99 mmol) in dry DMF was added NaN3 (0.76 g, 11.6 mmol).…”
Section: Experimental Section (2s5s)-5-o-methylsulfonyl-n-1 (Benzylox...mentioning
confidence: 99%
See 3 more Smart Citations
“…1 H NMR CDCl3 δ: 7.35(s, 5H), 5.2 (d, 2H), 5-4.75(m, 1H), 4.7-4.3 (m, H6), 3.7 (m, 3H), 3.1 (m, 3H), 2.5-1.4 (m, 5H). 13 (2S,5R)-5-Azido-N-1 (Benzyloxycarbonyl)pipecolic Acid Methyl Ester 3. To the compound 2 (0.74 g, 1.99 mmol) in dry DMF was added NaN3 (0.76 g, 11.6 mmol).…”
Section: Experimental Section (2s5s)-5-o-methylsulfonyl-n-1 (Benzylox...mentioning
confidence: 99%
“…These involved introduction of a methylene bridge between the R′ carbon atom of the glycyl moiety and the β/γ carbon atom of the aminoethyl/aminopropyl segment of the parent aeg/apgPNA to generate five-/six-membered pyrrolidine/piperidine rings. The comparative UV-T m studies after incorporation of these two modifications in a triplex forming aegPNAT 10 sequence showed that both (2S,4R) five- 12 and (2S,4S) six-membered 13 trans ring conformations caused detrimental effects on the stability of PNA 2 :DNA and thus were incapable of adopting the structural bias required for PNA 2 :DNA triplex formation. The primary knowledge of the stability of trans conformations in six-membered rings suggested that a trans-5-aminopipecolyl monomer (Figure 1,V) could be a better choice because of the stable, favored diequatorial disposition of the backbone.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4-Aminopipecolic acid has been found in the leaves of Strophantus scandens (Apocinaceae), [15Ϫ17] its stereochemistry not being assigned with certainty, and (2S,4S)-4-acetylamino pipecolic acid has been isolated from the leaves of Calliandra haematocephala (Leguminosae). [18] This amino acid moiety has been incorporated into different synthetic biologically active compounds such as cyclic peptides, [19Ϫ21] oligomers [22] and small molecules.…”
Section: Introductionmentioning
confidence: 99%